Percutaneous access planning, techniques and considerations for endovascular aortic repair (EVAR) - Vatakencherry, Geogy; Molloy, Chris; Sheth, Neil; Liao, Millie; Lam, Cuong Ken (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2018)
Percutaneous endovascular aortic repair (EVAR) has transformed the field of aortic repair. As techniques and devices improve, interventionalists continue to expand the boundaries of what is possible, enabling these life-saving procedures to be performed on a wider range of more technically challenging cases. This article discusses endovascular access considerations for EVAR including; ultrasound guidance, preclose technique, access vessel options, innovative devices, and bailout strategies that interventionalists should be familiar with to optimize patient outcomes.